RESPONS TUNAS KAKTUS (Mammillaria myriacantha) PADA BERBAGAI KONSENTRASI NAA DAN BAP SECARA IN VITRO - Mardhiah Hayati (Jurnal Floratek, 2008)
Response of shoot of cactus  (Mammillaria myriacantha) to various concentrations of NAA and BAP in Vitro Mardhiah Hayati Fakultas Pertanian Unsyiah Darussalam Banda Aceh ABSTRACT The research was arranged in a factorial completely randomized design 3 x 3 with 5 replicates. Factors evaluated were concentration of NAA (0, 2, 4 mgl-1), and concentration of BAP (0, 3, 6 mgl-1). Variables observed were initiation time, shoot numbers, shoot height, root number at 2 and 4 weeks after culturing (WAC) and life percentage, dead percentage, contamination percentage. The results showed that NAA significantly affected initiation time and shoot numbers at 4 WAC.  The best initiation time was found at concentration of  NAA 4 mgl-1 and the best shoot numbers was found at concentration of NAA 2 dan 4 mgl-1. BAP had significant effect on  shoot number 4 WAC, shoot height 2 WAC, and root numbers at 2 and 4 WAC.  The best shoot numbers and shoot height were found at  BAP 3 mgl-1 but did not significantly differ from BAP 6 mgl-1.  The best root numbers, however, was at no BAP.  There was no significant interaction between both factors.